Graphene Oxide-Modified Microcapsule Self-Healing System for 4D Printing - Ma, Bowen; Zhang, Yuping; Wei, Yongjie; Li, Mingrui; Li, Dongdong (Frontiers in Materials, 2021)
Self-healing materials as type of promising smart materials, are gradually applied into electronics, biology, engineering. In this work, we use in-situ polymerization to make melamine-formaldehyde resin (MF) microcapsules to wrap the epoxy resin as repairing agent, and Cu(MI)4Br2 as latent curing agent to cure epoxy resin E-51 from broken melamine-formaldehyde resin (MF) microcapsules. In addition, graphene oxide is used as reinforcing phase through its two-dimensional layered structure to improve the tensile strength to 41.91 MPa, which is higher than the initial materials. The melamine-formaldehyde capsules and latent curing agents are uniformly distributed in the materials according to the digital photos and SEM pictures. It is worth noting that the mechanical strength of the broken materials can be restored to 35.65 MPa after heating at 130 °C for 2 h to repair the damage, and the self-healing efficiency reached up to 85.06%. Furthermore, we also fabricated the 4D printed material with tensile strength of 50.93 MPa through a 3D printer. The obtained materials showed excellent repair effect with the recovery rate up to 87.22%. This work confirms that the designed self-healing system have potential applications in many areas due to their excellent self-healing performance, which provides valuable guidance for designing 4D system.